Comparison of The Effect of Topical Bromfenac With Nepafenac in Maintaining Mydriasis During Cataract Surgery - Garima Bansal; Surabhi Gupta; Sanjiv Kumar; Saurabh Kansal (Delhi Journal of Ophthalmology)
Obiective: To compare the effectiveness of prophylactic administration of topical nepafenac (0.1%) and bromfenac (0.09%) in maintaining mydriasis during cataract surgery. Methods: This was a randomized, double masked comparison study involving adult cataract patients given topical NSAIDs (nepafenac or bromfenac) or carboxymethylcellulose (control) prior to cataract surgery. Horizontal and vertical diameters of pupil were measured before and after surgery and the mean values were compared across the three groups. Results: The decrease in pupil size was more significant in group A (control) as compared to that in group B (nepafenac) and in group C (bromfenac) (p < 0.001). The decrease in pupil size was not significant in group B as compared to that in group C (p < 0.70). Mydriasis during surgery was well maintained in groups B and C as compared to group A. Conclusion: Both nepafenac (0.1%) and bromfenac (0.09%) given one day prior to the surgery are effective in maintaining pupil size during the cataract surgery but the less frequent dosing of bromfenac can be of advantage in improving the patient compliance.